Morphological support for placement of the Wing-banded Antbird Myrmornis torquata in the Thamnophilidae (Passeriformes: Furnariides) - Galvão, Ana; Gonzaga, Luiz Pedreira (Zootaxa, 2011)
Myrmornis torquata has often been considered an intermediate form between the ground antbirds and the typical antbirds. Although molecular phylogenies have consistently placed M. torquata in the Thamnophilidae (typical antbirds), this species has not been the subject of a thorough anatomical study, and no phylogeny based on morphological characters has been published. We undertook a cladistic morphological analysis of M. torquata and representatives of all families in the infraorder Furnariides, to clarify the systematic affinities of this species. In a parsimony analysis of 66 osteological and syringeal characters, Myrmornis clustered with other thamnophilids with high support values, sharing with them five synapomorphies of unambiguous optimization in all most-parsimonious trees. Two synapomorphies are syringeal features exclusive to the family: (1) the presence of processes on the ventral surface of supporting A-elements of the syrinx cranial to the membrana tracheosyringealis, and (2) the division of the musculus sternotrachealis into two fasciculi near its insertion on the syrinx. A third syringeal synapomorphy (presence of the musculus vocalis ventralis) also occurs in the Dendrocolaptidae and Furnariidae as a homoplasy. Two unambiguous osteological synapomorphies were found: (1) the narrowing of the foramen orbitonasale, and (2) the confluence of the foramen obturatum and the fenestra ischiopubica, a reversal also found in the Furnariidae. Our results provide strong morphological support for the placement of Myrmornis in the Thamnophilidae. Key-words: Morphological phylogeny, osteology, syrinx, suboscines, Furnarioidea, Thamnophilidae, Formicariidae, Grallariidae, Neotropics.